The expression and biological effect of NR2F6 in non-small cell lung cancer - Yang, Shu lin; Guan, Huan qin; Yang, Hong bao; Chen, Yao; Huang, Xiao ying; Chen, Lei; Shen, Zhi fa; Wang, Liang xing (Frontiers in Oncology, 2022)
Objective: This study aimed to explore the expression and effect of the nuclear receptor subfamily 2 group F member 6 (NR2F6) gene in non-small cell lung cancer (NSCLC) and provide an experimental basis for the targeted therapy of NSCLC. Method: First, the expression of NR2F6 in lung cancer tissues was analyzed using the Gene Expression Omnibus and the Cancer Genome Atlas (TCGA) databases, and the expression of NR2F6 in lung cancer tissues and cells was verified by Western blotting and quantitative polymerase chain reaction. Next, the relationship between NR2F6 expression and the clinicopathological features of lung cancer was analyzed via immunohistochemistry, and the relationship between NR2F6 expression and prognosis was analyzed using the Kaplan–Meier Plotter. The influence of NR2F6 knockdown on the proliferation capacity of lung cancer cells was then verified at cell level. Finally, the expression of heterogeneous nuclear ribonucleoprotein D (HNRNPD) in lung cancer tissue was analyzed using the TCGA database and immunohistochemistry. The impact of HNRNPD knockdown on the proliferation capacity of lung cancer cells was verified at cell level, and the relationship between NR2F6 and HNRNPD was verified by co-immunoprecipitation. Results: NR2F6 was highly expressed in lung cancer tissues and cells, and its expression was positively correlated with the depth of invasion, lymphatic metastasis, and clinical stage of lung cancer. High expression of NR2F6 in lung cancer was also significantly associated with poor prognosis. At cell level, NR2F6 knockdown was found to inhibit the proliferation of H460 and H358 in lung cancer cells. Furthermore, the TCGA database and immunohistochemical results showed that HNRNPD was highly expressed in lung cancer tissues and was highly consistent with NR2F6 expression in these tissues. Knockdown of HNRNPD also inhibited the proliferation of lung cancer cells. The co-immunoprecipitation experiment verified that NR2F6 interacted with HNRNPD. Conclusion: NR2F6 may interact with HNRNPD to jointly regulate the progression of lung cancer, and this conclusion provides a new experimental basis for the study of the molecular targeted therapy of NSCLC.